Focusing on exosomes to overcome the existing bottlenecks of CAR-T cell therapy - Si-Heng Zhang; Ling-Long Peng; Yi-Fei Chen; Yan Xu; Vahid Moradi (BMC, 2024)
Abstract Since chimeric antigen receptor T (CAR-T) cells were introduced three decades ago, the treatment using these cells has led to outstanding outcomes, and at the moment, CAR-T cell therapy is a well-established mainstay for treating CD19 + malignancies and multiple myeloma. Despite the astonishing results of CAR-T cell therapy in B-cell-derived malignancies, several bottlenecks must be overcome to promote its safety and efficacy and broaden its applicability. These bottlenecks include cumbersome production process, safety concerns of viral vectors, poor efficacy in treating solid tumors, life-threatening side effects, and dysfunctionality of infused CAR-T cells over time. Exosomes are nano-sized vesicles that are secreted by all living cells and play an essential role in cellular crosstalk by bridging between cells. In this review, we discuss how the existing bottlenecks of CAR-T cell therapy can be overcome by focusing on exosomes. First, we delve into the effect of tumor-derived exosomes on the CAR-T cell function and discuss how inhibiting their secretion can enhance the efficacy of CAR-T cell therapy. Afterward, the application of exosomes to the manufacturing of CAR-T cells in a non-viral approach is discussed. We also review the latest advancements in ex vivo activation and cultivation of CAR-T cells using exosomes, as well as the potential of engineered exosomes to in vivo induction or boost the in vivo proliferation of CAR-T cells. Finally, we discuss how CAR-engineered exosomes can be used as a versatile tool for the direct killing of tumor cells or delivering intended therapeutic payloads in a targeted manner.